Update of the scientific evidence for specifying lower limit relative humidity levels for comfort, health, and indoor environmental quality in occupied spaces (RP-1630) - Derby, Melanie M.; Hamehkasi, Maryam; Eckels, Steven J.; Hwang, Grace M.; Jones, Byron; Maghirang, Ronaldo; Shulan, David (My University, 2016)
Nearly 600 articles were located in citation and keyword searches regarding the effects of humidity on comfort, health, and indoor environmental quality. Of these, around 70 articles reported the effects of low humidity (relative humidity ≤ 40%) and were analyzed in detail. Information in some categories was well chronicled, while other categories had significant knowledge gaps. Low humidity decreased house dust mite allergens. Due to different envelopes, generalizations could not be made for all bacteria and viruses. However, lower humidity increased virus survival for influenza. For comfort, low humidity had little effect on thermal comfort, but skin dryness, eye irritation, and static electricity increased as humidity decreased. For indoor environmental quality, low humidity had nonuniform effects on volatile organic compound emissions and perceived indoor air quality. Across many low humidity studies, ventilation rates and exposure times were noted as confounding variables. A majority of studies that used human subjects utilized exposure times of 3 h or less with adult subjects; few studies used children, adolescents, or elderly subjects.
Citation: M.M. Derby, M. Hamehkasi, S. Eckels, G. Hwang, B. Jones, R. Maghirang, D. Shulan, Update the Scientific Evidence for Specifying Lower Limit Relative Humidity Levels for Comfort, Health and IEQ in Occupied Spaces (1630-RP), Science and Technology for the Built Environment, (2016), DOI: http://dx.doi.org/10.1080/23744731.2016.1206430